Application of cider by-products for medium chain length polyhydroxyalkanoate production by Pseudomonas putida KT2440. (November 2018) - Urbina, Leire; Wongsirichot, Phavit; Corcuera, María Ángeles; Gabilondo, Nagore; Eceiza, Arantxa; Winterburn, James; Retegi, Aloña
Graphical abstract: Highlights: Use of cider waste for the production of PHA by Pseudomonas putida KT2440. The raw material contains two main residual sugars, glucose and fructose. PHA concentration of 1.1 g L −1 and PHA accumulation of 25.5% were obtained. mcl-PHA copolymer with elastomeric characteristics was extracted from the biomass. Abstract: In this study the technical feasibility of using cider by-products as a substrate for the production of medium chain length polyhydroxyalkanoates (mcl-PHAs) by Pseudomonas putida KT2440 is demonstrated. The untreated apple pomace was found to be composed of two main residual sugars, glucose and fructose, making it a promising cheap growth substrate. A PHA concentration of 1.1 g L −1 and a PHA accumulation of 25.5% were obtained in flask experiments using apple pomace as the sole carbon source without any pretreatment, employing a fed batch strategy. The biopolymer was extracted from the biomass and a detailed characterization was carried out. The solution-casted film was found to be a mcl-PHA copolymer composed by different saturated and unsaturated ester monomers with elastomeric characteristics making it suitable for applications in biomedicine or the processing of value added co-products such as environmentally friendly adhesives or biodegradable films for agricultural purposes.